Phytochemical Screening and Antibacterial Activity of Kratom Leaf (Mitragyna speciosa Korth.) Against Aeromonas hydrophilla - Juanda, Eki; Andayani, Sri; Maftuch, Maftuch (Graduate School, Universitas Brawijaya, 2019)
Kratom (Mitragyna speciosa) is an indigenous tropical herbal plant to the Northern Malay Peninsula and Thailand. Empirically kratom leaves have several properties as herbal medicines. Currently, the treatment of diseases caused by bacteria that are resistant to antibiotics requires new compounds that have high potential. The material studied was kratom leaf extract. The solvent used for extraction is methanol. Phytochemical screening carried out includes the examination of alkaloids, flavonoids, steroids/terpenoids, phenols, tannins, and saponins. The test bacteria used was Aeromonas hydrophilla. The medium used is Nutrient Agar (NA). NaCl 0.9% as a bacterial suspension. Testing the antibacterial activity carried out with 10 (ten) variations of concentration namely 3%, 6%, 9%, 12%, 15%, 18%, 21%, 24%, 27% and 30 %. Fresh kratom leaf is collected and then wet sorted. The extraction process was using the method of maceration. This study aims to analyze the antibacterial activity of kratom leaf, measure the secondary compounds of kratom leaf extract, and measure the best concentration to kill Aeromonas hydrophilla. The extraction process obtained blackish-brown extract with 62.27 grams of extract (31.14%). Secondary metabolites of kratom leaf extract show positive results of alkaloid, saponins, tannins, phenolics, steroids, and triterpenoids. Antibacterial activity against Aeromonas hydrophila which is characterized by a kill zone around the paper disc with the best concentration that shows a wide killing zone was 24% of the extract.Keywords: Antibacterial, Extract, Kratom, Mitragynine, Phytochemical Screening.